The analytic expressions of sensitivity parameters for fiber-optic refiective system - Kleiza, Vytautas; Verkelis, Jonas (Lietuvos matematikos rinkinys, 2004)
In this work the analytic expressions of absolute maxima and envelope for family of signals curves have found, which are more accurate than experimental data.
Keywords: fiber-optic reflective; sensitivity; absolute maxima; analytic expressions